Does Repolishing Affect the Gloss and Roughness of Lithium Disilicate and Monolithic Zirconia Ceramics? - Cigdem Cebi Tuysuz; Necla Demir; Emir Yuzbasioglu (Applied Sciences)
Purpose Maintaining the surface quality of ceramic restorations after clinical adjustments is critical for both aesthetic outcomes and long-term oral health, yet the optimal approach to restoring gloss and smoothness remains unclear. The purpose of this study is to investigate the effect of different surface finishing and grinding procedures on the surface gloss and roughness of three different monolithic lithium disilicate ceramics and one monolithic ultra-translucent zirconia ceramic. Materials and Methods A total of 104 specimens (1.5 × 12 × 14 mm) were prepared from four ceramic materials: LiSi CEREC Tessera (CT), GC Initial LiSi (LS), IPS e.max CAD (EC), and zirconia disc (KATANA UTML (KAT)). Each was divided into two subgroups based on surface finishing (mechanical polishing or glazing; n = 10). Gloss and surface roughness were measured using a glossmeter and a profilometer, respectively. One specimen per subgroup was analyzed under SEM at ×1000 magnification. Results Gloss and roughness values were analyzed with the two-way robust ANOVA test and multiple comparisons were made with Bonferroni correction. The significance level was set at p < 0.05. Mechanical polishing, glazing, and repolishing increased the gloss values of the materials, with the KAT group achieving the highest gloss in the repolishing groups. The lowest gloss values were observed in the grinding groups. Additionally, these surface treatments reduced the roughness of the surface of all the materials. Conclusions Surface finishing procedures significantly influenced the gloss and roughness of monolithic lithium disilicate and zirconia ceramics. Mechanical polishing systems performed similarly or better than glazing. However, selecting an appropriate polishing system for each material is essential.